SAT0142 Predictors of inadequate response and rapid radiographic progression in patients with early rheumatoid arthritis receiving methotrexate: a post hoc analysis of 2 randomized, controlled trials of adalimumab. (15th June 2017) - Kavanaugh, A; Vollenhoven, RF van; Wolfe, BA; Florentinus, S; Chen, S; Suboticki, JL; Smolen, JS
Abstract : Background: Methotrexate (MTX) is recommended as first-line therapy in patients (pts) with rheumatoid arthritis (RA). 1 However, information is limited regarding factors that may predict a poor response to MTX. Objectives: To identify predictors of MTX insufficient response (IR) and rapid radiographic progression (RRP) among pts with early RA receiving 6 months (mos) of MTX therapy. Methods: In OPTIMA, pts with RA <1 year were randomized to receive either adalimumab (ADA) 40 mg every other wk (EOW) + MTX weekly (wkly) or placebo (PBO) EOW + MTX wkly for 26 wks. In PREMIER, pts with RA <3 years were randomized to receive ADA 40 mg EOW + MTX wkly, ADA 40 mg EOW + PBO wkly, or PBO EOW + MTX wkly for 2 years. This post hoc analysis compared MTX-IR pts, defined as not reaching stable low disease activity at wks 22 and 26 in OPTIMA and wks 20 and 24 in PREMIER, with pts who responded to initial MTX monotherapy. Comparisons were also made between pts who did and did not have RRP, assessed by an increase in modified Total Sharp Score (mTSS) of >1.5 from baseline (BL) to 6 mos. In pts with available data, backward logistic regression was used to identify potential predictors of MTX-IR and RRP. Candidate predictors included BL demographics, time-averaged disease parameters for 3 time intervals (through 4 wks, 8 wks, and 12 wks of MTX exposure), and BL disease characteristics for the 12-wk interval. Time-averaged variables were calculated as area under the curve standardized for length of time interval. Results: This analysis included 525 MTX-IR and 162 MTX responders. Mean disease duration at BL was 6 mo for both groups. The mean Disease Activity Score 28 (C-reactive protein; DAS28[CRP]) was 6.2 vs 5.6, Health Assessment Questionnaire Disability Index (HAQ-DI) was 1.6 vs 1.3, and mTSS was 15.5 vs 12.2 for MTX-IR vs MTX responders, respectively. 171 pts experienced RRP, while 499 pts had no RRP; the mean disease duration at BL was 6 mo for both groups. The mean DAS28(CRP) was 6.4 vs 6.0 and HAQ-DI was 1.6 vs 1.5 for pts experiencing RRP vs pts who did not experience RRP, respectively. Mean mTSS at BL was higher for pts who experienced RRP (20.7) vs those who did not (12.4). Predictors of MTX-IR and RRP at 6 mos are shown in the Figure. Time-averaged HAQ-DI and DAS28(CRP) through 12 wks were the strongest predictors of both MTX-IR and RRP. Additionally, early clinical response (time-averaged DAS28[CRP]) at both 4 and 8 wks was predictive of both MTX-IR and RRP; however, time-averaged HAQ-DI was not predictive until wk 12. Conclusions: In the OPTIMA and PREMIER trials, post-BL measures of RA activity appeared to be the strongest predictors of subsequent MTX-IR and of RRP. Pts who are likely to progress on MTX or have RRP may be good candidates for switching to earlier step-up therapy to reduce the likelihood of permanent bone damage. References: Singh JA, et al. Arthritis Care Res (Hoboken). 2016;68(1):1–25. Acknowledgements: AbbVie: study sponsor, contributed to design, data collection, analysis, interpretation; and (funded) writing, reviewing, approval of final version. Medical writing: Y.E. Yarker, M.J. Theisen, Complete Publication Solutions, LLC. Disclosure of Interest: A. Kavanaugh Grant/research support from: AbbVie, Amgen, AstraZeneca, BMS, Celgene, Centocor-Janssen, Pfizer, Roche, and UCB, Consultant for: AbbVie, Amgen, AstraZeneca, BMS, Celgene, Centocor-Janssen, Pfizer, Roche, and UCB, Speakers bureau: AbbVie, Amgen, AstraZeneca, BMS, Celgene, Centocor-Janssen, Pfizer, Roche, and UCB, R. F. van Vollenhoven Grant/research support from: AbbVie, Amgen, BMS, GSK, Pfizer, Roche, and UCB, Consultant for: AbbVie, Biotest, BMS, Crescendo, GSK, Centocor-Janssen, Lilly, Merck, Pfizer, Roche, UCB, and Vertex, B. A. Wolfe Shareholder of: AbbVie, Employee of: AbbVie, S. Florentinus Shareholder of: AbbVie, Employee of: AbbVie, S. Chen Shareholder of: AbbVie, Employee of: AbbVie, J. L. Suboticki Shareholder of: AbbVie, Employee of: AbbVie, J. S. Smolen Grant/research support from: AbbVie, Consultant for: AbbVie, Speakers bureau: AbbVie